Insulin promotes invasion and migration of KRASG12D mutant HPNE cells by upregulating MMP‐2 gelatinolytic activity via ERK‐ and PI3K‐dependent signalling. (5th March 2019) - Wang, Guangfu; Yin, Lingdi; Peng, Yunpeng; Gao, Yong; Gao, Hao; Zhang, Jingjing; Lv, Nan; Miao, Yi; Lu, Zipeng
Abstract: Objectives: Hyperinsulinemia is a risk factor for pancreatic cancer, but the function of insulin in carcinogenesis is unclear, so this study aimed to elucidate the carcinogenic effects of insulin and the synergistic effect with the KRAS mutation in the early stage of pancreatic cancer. Materials and methods: A pair of immortalized human pancreatic duct‐derived cells, hTERT‐HPNE E6/E7/st (HPNE) and its oncogenic KRAS G12D variant, hTERT‐HPNE E6/E7/ KRAS G12D /st (HPNE‐mut‐ KRAS ), were used to investigate the effect of insulin. Cell proliferation, migration and invasion were assessed using Cell Counting Kit‐8 and transwell assays, respectively. The expression of E‐cadherin, N‐cadherin, vimentin and matrix metalloproteinases (MMP‐2, MMP‐7 and MMP‐9) was evaluated by Western blotting and/or qRT‐PCR. The gelatinase activity of MMP‐2 and MMP‐9 in conditioned media was detected using gelatin zymography. The phosphorylation status of AKT, GSK3β, p38, JNK and ERK1/2 MAPK was determined by Western blotting. Results: The migration and invasion ability of HPNE cells was increased after the introduction of the mutated KRAS gene, together with an increased expression of MMP‐2. These effects were further enhanced by the simultaneous administration of insulin. The use of MMP‐2 siRNA confirmed that MMP‐2 was involved in the regulation of cell invasion. Furthermore, there was a concentration‐ and time‐dependent increase in gelatinase activity after insulin treatment, which could be reversed by an insulin receptor tyrosine kinase inhibitor (HNMPA‐(AM)3 ). In addition, insulin markedly enhanced the phosphorylation of PI3K/AKT, p38, JNK and ERK1/2 MAPK pathways, with wortmannin or LY294002 (a PI3K‐specific inhibitor) and PD98059 (a MEK1‐specific inhibitor) significantly inhibiting the insulin‐induced increase in MMP‐2 gelatinolytic activity. Conclusions: Taken together, these results suggest that insulin induced migration and invasion in HPNE and HPNE‐mut‐ KRAS through PI3K/AKT and ERK1/2 activation, with MMP‐2 gelatinolytic activity playing a vital role in this process. These findings may provide a new therapeutic target for preventing carcinogenesis and the evolution of pancreatic cancer with a background of hyperinsulinemia.